(untitled) (INNOVATIVE ECONOMY, 2025)
Kolesnikov A.V. ANALYSIS OF THE EXTERNAL ECONOMIC PARAMETERS OF UKRAINE’S FLORICULTURE MARKET AS FACTORS OF THE RECOVERY ECONOMY Purpose. The aim of the article is to analyse the foreign economic parameters of the floriculture market in Ukraine in the context of considering the industry as one of the priorities in the recovery economy. Methodology of research. The theoretical and methodological basis of the research is the systemic approach to the consideration of social and economic phenomena and processes. During the study, other methods were also used, in particular: the statistical method – for assessing the trends in changes in the volumes of import and export of floriculture products by foreign economic codes of the Ukrainian Classification of Goods for Foreign Economic Activity (UCGFEA codes); the abstract and logical method – for understanding the regularities of manifestation of import and export trends of floriculture products; the tabular method – for the visual presentation of the research results; the generalization method – for formulating the research conclusions. Findings. The important role of floriculture as a flexible and labour-intensive sector in the conditions of the recovery economy has been determined. The trends of floriculture product imports into Ukraine during the period 2020–2024 have been generalized, and four stages of its development have been identified: import growth (2021), import reduction (2022), adaptation (2023), and import recovery (2024). The trends of floriculture product exports from Ukraine have been generalized, and three predominant stages of its development have been identified, with the manifestation of an export growth trend in the first stage (2021), export reduction in the second stage (2022–2023), and the beginning of adaptation (2024). A negative balance of foreign trade in floriculture products has been established, which actualizes the need for institutional support for the expansion of domestic production, export, and import substitution. Originality. The approach to the analysis of foreign economic trends of floriculture products has been improved. It takes into account the differentiated characteristics of the analysis results by general indicators of the volume of import and export of floriculture products in Ukraine, in terms of four types of floriculture products (Ukrainian classifier of goods of foreign economic activity (UCGFEA 0601 “Bulbs, tubers, rhizomes), ”UCGFEA 0602 “Other live plants; mushroom mycelium,” UCGFEA 0603 “Cut flowers and flower buds,” and UCGFEA 0604 “Foliage, branches, grasses, mosses, and lichens”). The approach also considers the trends by stages of export development (growth, reduction, beginning of adaptation) and import (growth, reduction, adaptation, recovery). In contrast to the existing approaches, this will make it possible to prepare more substantiated documents on various issues of the development of the floriculture sector and the floriculture products market. Practical value. The research results can be used in conducting analytical work and substantiating measures in strategic and program documents on the development of the floriculture sector and the floriculture products market, in particular, when identifying strategic directions for forming a model of floriculture development focused on adaptability, export prospects, and integration into the recovery economy. Key words: floriculture, floriculture products market, import, export, foreign trade balance, recovery economy, import substitution.